Hubungan Antara Konformitas di Lingkungan Pertemanan dengan Gaya Hidup Hedonisme pada Pelajar SMA - Herwina septiana Putri; Bernardinus Agus Arswimba (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is quantitative correlational research. The research aims to determine the relationship between conformity in the social environment and the hedonistic lifestyle of high school students and to find out how high the level of conformity and hedonism is. Subjects numbered 70 students. Data collection used a conformity scale with 22 valid items with a reliability test value of 0.877 and a hedonism scale with 26 valid items with a reliability test value of 0.871. The research results show that there is a negative relationship between conformity and hedonism with a high level of significance with an r value of = 0.163 and p=0.177. The level of conformity is classified in the very high category with a percentage of 87%. The level of hedonism is classified as low with a percentage of 57%. Based on these results, it can be seen that the higher the level of conformity, the level of hedonism tends to decrease, and vice versa.